Rule talk: instructing proper play with impersonal deontic statements - Zinken, Jörg; Kaiser, Julia; Weidner, Matylda; Mondada, Lorenza; Rossi, Giovanni; Sorjonen, Marja-Leena (Frontiers in communication, 2021)
The present paper explores how rules are enforced and talked about in everyday life. Drawing on a corpus of board game recordings across European languages, we identify a sequential and praxeological context for rule talk. After a game rule is breached, a participant enforces proper play and then formulates a rule with an impersonal deontic statement (e.g. “It’s not allowed to do this”). Impersonal deontic statements express what may or may not be done without tying the obligation to a particular individual. Our analysis shows that such statements are used as part of multi-unit and multi-modal turns where rule talk is accomplished through both grammatical and embodied means. Impersonal deontic statements serve multiple interactional goals: they account for having changed another’s behavior in the moment and at the same time impart knowledge for the future. We refer to this complex action as an “instruction.” The results of this study advance our understanding of rules and rule-following in everyday life, and of how resources of language and the body are combined to enforce and formulate rules.